Influência da preocupação com quedas na mobilidade e na força de reação do solo em idosas durante descida de escada - Silva, Danilo de Oliveira [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; de Oliveira, Maíra Caroline; Aragão, Fernando Amâncio; de Albuquerque, Carlos Eduardo (EDIPUCRS, 2016)
Aims: To investigate the difference between elderly women with and without concern about falls in mobility and vertical ground reaction force during stair descent. Methods: The study included older women assisted in the Centre for Physical Rehabilitation of the Universidade Estadual do Oeste do Paraná, aged between 60 and 75 years, without neurological and cardiovascular disease involving risk by the activities of the study. Women with orthoses for locomotion, osteoarticular diseases or surgery of lower limbs, and previous fall history were also excluded. The participants were divided into two groups, with and without concern about falls in daily activities, identified by the Falls Efficacy Scale International translated into Portuguese. To assess mobility, all subjects performed the Timed Up and Go Test. Ground reaction force was assessed by walking steps down five times to collect kinetic data (first peak of the vertical ground reaction force) through a force platform allocated in the fourth step of a staircase of seven steps. After confirmed normality of data, Student t test for independent samples was used to compare the groups. Results: The sample was composed of seventeen elderly women with no concern about falling (aged 66.57±4.1 years) and sixteen elderly women with concerns about falling (aged 66.67±5.8 years). The group without concern with falls performed the Timed Up and Go Test faster (9.71±1,02 seconds) than the group with concern about falls (11.5±1,04 seconds) (p=0.008). There was no difference between groups on the first peak of vertical ground reaction force (p=0.66). Conclusions: Elderly women with concern about falls had lower performance in the functional test than elderly women with no such concern. However, there was no difference between the groups in terms of the kinetic variable.
Influence of concern about falls in mobility and ground reaction force in elderly women's during stairs descent
Keywords: Elderly; Fear; Kinetics; Locomotion; Questionnaires